ANALYSIS OF FACTORS AFFECTING THE TRANSPARENCY OF REGIONAL FINANCIAL INFORMATION IN REGIONAL GOVERNMENT OF PANGKEP DISTRICT - Sari, Dewi; Yusuf, Marwah; Amin, Asbi (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2023)
ABSTRACT Purpose – This study aims to determine and analyze the presentation of financial, and internal controls that statements, accessibility affect the transparency of regional financial information Design/methodology/approach – This study using quantitative research methods with descriptive statistics Findings – The results of this study indicate: (1) prepare monetary accountability for general purposes (broadly useful fiscal summaries) to build equality of monetary accountability both for funding plans, between periods, and between substances and (2) Inward control is characterized as a cycle that is influenced by a group of head leaders, heads or top administration, other faculties, which is intended to obtain sufficient confirmation about the achievement of goals. Originality – The population in Regency regional apparatus the study in Pangkep district governments These are the entire Pangkep organization, in study is 54 people, device totaling 41 agencies Keywords: Presentation of Financial Statements, accessibility, Internal Control Paper Type Research Result